If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = 6x + 7x + 9 Reorder the terms: -4 = 9 + 6x + 7x Combine like terms: 6x + 7x = 13x -4 = 9 + 13x Solving -4 = 9 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -4 + -13x = 9 + 13x + -13x Combine like terms: 13x + -13x = 0 -4 + -13x = 9 + 0 -4 + -13x = 9 Add '4' to each side of the equation. -4 + 4 + -13x = 9 + 4 Combine like terms: -4 + 4 = 0 0 + -13x = 9 + 4 -13x = 9 + 4 Combine like terms: 9 + 4 = 13 -13x = 13 Divide each side by '-13'. x = -1 Simplifying x = -1
| 8*(2p-4)*3p=20 | | 6x+1+5x=-65 | | a+10=b+2 | | 1+2x=x-2-4x | | -2x-5y=-27 | | 14(d+30)=-196 | | -4+4x-5x=-14 | | 3f=(2f+8) | | 6X-12+4X-1=-X+12-3X+5 | | x+(x+10)+2x=98 | | 4x+3=x+x+29 | | 2t-1=2t-5 | | 4y+3=y+21 | | 4y+3=y+22 | | 625-25x=0 | | (35x+67y)+(-20x+41y)= | | f(x-1)=x^2+3 | | f(x-1)=x^2-3 | | 14d+30=196 | | 14z=3(4z+3) | | 10x^3-11x^2-6x=0 | | 2x-1+3=4 | | 32=-0.8m | | -3.2x=14.4 | | -1.25+.25x=0 | | -1.25+25x=0 | | x+(-26)=52 | | 3x^4+12x^2=12x^3 | | -x^2+32=(X+4)(X-4) | | 2x+2=10-8x | | 314=n+576 | | y=-5x^2+23x |